Semi-continuous anaerobic treatment of fresh leachate from municipal solid waste transfer station - Ghasimi, Seyed Mohammad Dara; Idris, Azni; Chuah, Teong Guan; Tey, Beng Ti (Academic Journals, 2009)
A semi-continuous leachate treatment process was developed in the present study. The fresh leachate was obtained from a municipal solid waste transfer station and palm oil mill effluent (POME) sludge was used as sources of anaerobic microbial complex. The semi-continuous treatment of leachate was operated in two phases; in Phase 1, the pH of the bioreactor was not adjusted, and in Phase 2, the pH of the bioreactor was adjusted by the addition of sodium hydroxide (NaOH). The initial values for both chemical oxygen demand (COD) and biochemical oxygen demand (BOD5) of fresh leachate were extremely high compared with the stabilized landfill leachate. COD reduction rate for the semicontinuous process for Phase 1 and 2 were 37 and 52.7%, respectively. These results clearly showed that pH adjustment is important to enhance the COD removal in leachate treatment. In addition, we have analysed the evolution of volatile fatty acid (VFA) in the entire treatment process. The results indicated that the VFA concentration was a rapid indicator of the reactor’s stability.